Exploitation of porphyrin-based titanium-rich porous organic polymers for targeted phosphopeptide enrichment from the serum of colorectal cancer individuals - Wang, Danni; Sheng, Xiuqin; Shao, Jiahui; Ding, Chuan-Fan; Yan, Yinghua (Mikrochimica acta (1966), 2024)
A porphyrin-based titanium-rich porous organic polymer (Th-PPOPs@Ti 4+ ) was designed based on immobilized metal ion affinity chromatography technique and successfully applied to phosphopeptide enrichment with 5,10,15,20-tetrakis(4-carboxyphenyl) porphine tetramethyl ester (TCPTE), 2,3-dihydroxyterephthalaldehyde (DHTA), and 2,3,4-trihydroxybenzaldehyde (THBA) as raw materials. Th-PPOPs@Ti 4+ exhibited remarkable sensitivity (0.5 fmol), high selectivity (β-casein: BSA = 1:2000, molar ratio), outstanding recovery (95.0 ± 1.9%), reusability (10 times), and superior loading capacity (143 mg·g −1 ). In addition, Th-PPOPs@Ti 4+ exhibited excellent ability to specifically capture phosphopeptides from the serum of colorectal cancer (CRC) individuals and normal subjects. Sixty phosphopeptides assigned to 35 phosphoproteins were obtained from the serum of CRC individuals, and 43 phosphopeptides allocated to 28 phosphoproteins were extracted in the serum of healthy individuals via nano-LC–MS/MS. Gene ontology assays revealed that the detected phosphoproteins may be inextricably tied to CRC-associated events, including response to estrogen, inflammatory response, and heparin binding, suggesting that it is possible that these correlative pathways may be implicated in the pathogenesis of CRC. Graphical Abstract